KNOWLEDGE AND USE OF MODERN CONTRACEPTIVES AMONG MOTHERS OF REPRODUCTIVE AGE IN ENUGU STATE; SOUTHEASTERN NIGERIA - UCHENNA TERESA OKONKWO; HELEN NNADI; CHIOMA AKAEBE (International Studies Journal)
Evidence from various studies shows that there is a high level of knowledge and awareness of contraceptive methods in Nigeria, yet the rate of use remains low. This study explored broadly the level of knowledge and extent of utilization of modern contraceptives among mothers of reproductive age in Enugu State, Southeastern Nigeria. Questionnaires (n=1200), in-depth interviews (n=6), and focus group discussions (n=96) were used to collect data from three local government areas (LGAs). The results showed high levels of knowledge (87.0%). However, only 47.0% used a type of modern contraceptive. The oral contraceptive pill was the highest mentioned (333 mentions) of modern contraceptives. Chi-square values showed that level of education, type of residence, number of living children, and income were significantly related to the use of modern contraceptives and that mothers of reproductive age with higher education (secondary and tertiary) tended to use modern contraceptives more than their counterparts. Urban residents used modern contraceptives more than the ruralites. The number of living children also influenced the use of modern contraceptives, and income also influenced the use of modern contraceptives because the higher the income of a mother of reproductive age in Enugu State, the more likely she may use a modern contraceptive (p< 0.05). Qualitative data indicated that the majority of married mothers of reproductive age who used any other modern contraceptive aside from the male condom often do so without the knowledge or consent of their spouses due to male dominance and some patriarchal values/beliefs. This study highlights the need for males to be actively involved in the reproductive health of females and helps to understand the essence of the use of modern contraceptives; this will invariably increase the utilization of modern contraceptives among mothers of reproductive age in Enugu State, Southeastern Nigeria. Finally, this study is different from various related studies because it revealed that male dominance is a major cultural factor that impedes the usage of modern contraceptives, unlike other studies that may focus on the fear of side effects.